MODELING USE IN A SYSTEM FOR REUSE OF WASTEWATER FOR IRRIGATION: A CASE STUDY - BROTA, GIOVANI .A; CORAUCCI FILHO, BRUNO; ROSTON, DENIS MIGUEL; LUCAS JAQUIÊ RIBEIRO, LUBIENSKA CRISTINA; GUILHERME PIRES, MARTA SIVIERO (Revista Brasileira de Engenharia de Biossistemas, 2009)
Although irrigation is drip by drip, water consumption continues to increase and sources of drinkingwater are running low. One can see that the underground aquifers are drying up and the river levelsare decreasing and it is evident that the rainfall is decreasing. Water scarcity may affect thousands ofpeople in the very near future. Resource management is essential in the current situation anddeveloping new supplier sources to meet all this consumerism of human’s beings that use high levelsof water is a need. The human being knows about abusive water usage and knows that it is not lateto change this reality. How to deal with these problems without affecting human development andmaintain quality of life is the big issue. It was with the idea to rethink about humans actions andexternalize their ideas and thoughts that this research presents the semi-quantitative and quantitativemodel about the use of natural systems of wastewater treatment. With the advancement of the use ofcomputer modeling tools one can have a structure that helps to give expression to the thought andcoupe to think about new situations.